Effectiveness of Digital Interventions in Reducing Occupational Stress: A Systematic Review - Bima Indra; Valie Palmasutra; Febry Afrianto Setyawan (Karger Publishers, 2024)
Occupational stress is the response people may have when presented with work demands and pressures that are not matched to their knowledge and abilities, challenging their ability to cope. It is a pervasive concern in modern work environments, impacting workers' well-being and organizational productivity. Current available methods to manage workers' stress include providing psychologist consultations and using digital intervention. Digital interventions, including smartphone apps and website programs, have emerged as accessible tools for stress reduction. However, there is a need to assess their effectiveness systematically. A systematic review encompassed randomized controlled trials (RCTs) from the inception to May 2024. A comprehensive search in four electronic databases identified 15 eligible RCTs. Of a total of 15 included studies, all studies demonstrated a significant reduction in occupational stress with the use of digital interventions. Interventions varied in duration, frequency, and delivery platforms, with smartphone-based applications being predominant. Common intervention components included meditation, coping stress management, and nutritional and exercise content. Positive effects on worker mental health were observed to persist for up to 3-12 months post-intervention. The findings underscore the potential of digital interventions to promote employee well-being and contribute to healthier and more productive work environments. Digital interventions offer promising avenues for addressing occupational stress and promoting worker well-being.